TECNOLOGIA ALTERNATIVA PARA PRODUÇÃO DE SEMENTES DE INHAME (Dioscorea cayennensis) E SEU DESEMPENHO NO RENDIMENTO E QUALIDADE DE TÚBERAS - Eliziário, Daniel Ferreira de Lima (2015)
The current seed production system of yam is through cut, which process is costly and requires skilled labor. The ideal seed for yam cultivation is that whole or part of the head (for contain a large number of buds sprouting, considered high quality and for standardize the stand) with a mean weight of 200 g, produced with relatively low cost. The project was conducted in the experimental area of the University Federal of Paraíba, in Areia, with the objective of evaluate alternative system for seed production of yams and their performance in the yield and in the quality of tubers. The experimental design used in each step was a randomized block with treatments distributed in a scheme factorial 4 x 9, with masses of factors tuber-seeds 50, 100, 150 and 200 g and spacing of 10 x 10 cm, 10 x 15 cm, 15 x 15 cm, 20 x 10 cm, 20 x 15 cm, 20 x 20 cm, 25 x 10 cm, 25 x 15 cm and 25 x 25 cm, in three replicates. Therefore, the project was executed in two stages. The first entailed in seed production by means of density planting of parts of the tuber-seeds with different weights. In this step were taken the data the average weight and of the tuber-seeds production. In the second stage the tuber-seeds produced in the previous step were planted on the pitch to evaluate the yield and the quality of tubers of the yam, spaced 1.20 x 0.60 m. In this step were evaluated, average weight of commercial tubers, commercial and total yield of tubers, percentage of tubers with symptoms of nematode and quality of tubers. The data obtained were subjected to analysis of variance and regression, using the test F to comparison the mean squares and the averages compared by Scott Knott test at 5% probability. In accordance with the results in the first step there was effect of the weights of the portions of tuber-seeds on the seed average weight and production and the spacings only altered the seed weight. The average seed weight has achieved maximum value of 130 g with the use of the portion of the tuber-seeds of 115 g and the seed maximum productivity was 4.3 t ha-1 in portion of in 200 g of tuber-seeds. The highest values for the average seed weight were achieved in greater spacings. In the second stage the weights of portions of tuber-seeds changed the weight average, the productivity of tubers, and the percentage of tuber-seeds with symptoms of nematode attack. The average weight of tubers showed a maximum value of 2.0 kg, in portion 200 g. The total productivity of tubers presented an average of 13.5 t ha-1 and the productivity marketable of 12.2 t ha-1 in the portion of tuber-seeds of 170 g. The major portions of tuber-seeds induced an increase in percentage of tubers with symptoms of nematode attack.